Cardiac Plug I and Amulet Devices: Left Atrial Appendage Closure for Stroke Prophylaxis in Atrial Fibrillation - Parashar, Akhil (J Atr Fibrillation, 2015)
Percutaneous left atrial appendage (LAA) occlusion has emerged as an exciting and effective modality for stroke prophylaxis in patients with non-valvular atrial fibrillation who are deemed too high risk for anticoagulation with warfarin or newer anticoagulants. The Amplatzer devices have been used in LAA occlusion for more than a decade, starting with off label use of an atrial septal occluder device for LAA occlusion. This was followed by introduction of a dedicated Amplatzer cardiac plug (ACP) 1 for LAA occlusion, and more recently, the second generation Amulet device, with reported better stability enhancing features, has been introduced. Both these devices are widely used outside the United States, however in the US only the WATCHMAN device has been FDA approved. Unlike the WATCHMAN device, where the evidence is continuously building as the data from two pivotal randomized controlled trials are emerging, most of the evidence for ACP devices is from pooled multicenter registry data. In this article, we review the device design, implantation techniques and the most recently published evidence for both the Amplatzer cardiac plug 1 and the newer Amulet device. Our goal is to summarize the most recent literature and discuss the current role of the Amplatzer devices in the exciting and rapidly growing field of percutaneous LAA occlusion.